1992
DOI: 10.1080/01952307.1992.11735857
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Adjustment to Spinal Cord Injury

Abstract: Individuals with spinal cord injury were studied in 1974 (N = 256), 1985 (N = 347) and 1989 (N = 286) using the Life Situation Questionnaire (LSQ). The latter surveys included nearly all of the surviving participants from the 1974 sample plus a new sample of individuals with more recent injuries. Items covered activities, frequency of medical treatment, ratings of satisfaction with various aspects of life, ratings of problem areas, and judgments regarding personal adjustment to SCI. Subjects were grouped accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 3 publications
2
37
1
Order By: Relevance
“…This indicates that individual attitudes toward people with disabilities and the injured person's own prejudices of physical deviance may in some cases make it dicult to develop new relationships or re-establish old ones. The number of partner relationships contracted after injury among both SCI and TBI persons indicates, however, that the injury is not a major barrier to establishing close partner relationships, which is consistent with the study of Berkman et al 40 Crewe and Krause 41 found that only individuals who are especially likeable, active and well adjusted succeed in attracting partners and establishing close relationships after an SCI. The authors found in a later study 42 that SCI persons who get married after injury were more active both socially and vocationally during their single days compared to those who remained single.…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that individual attitudes toward people with disabilities and the injured person's own prejudices of physical deviance may in some cases make it dicult to develop new relationships or re-establish old ones. The number of partner relationships contracted after injury among both SCI and TBI persons indicates, however, that the injury is not a major barrier to establishing close partner relationships, which is consistent with the study of Berkman et al 40 Crewe and Krause 41 found that only individuals who are especially likeable, active and well adjusted succeed in attracting partners and establishing close relationships after an SCI. The authors found in a later study 42 that SCI persons who get married after injury were more active both socially and vocationally during their single days compared to those who remained single.…”
Section: Discussionsupporting
confidence: 80%
“…1,2 The spouse is the key support person for many persons with SCI and a good marriage is a primary source of physical as well as emotional support. [3][4][5][6] It is probably for this reason that being married is a powerful predictor of adjustment and quality of life of persons with SCI. [6][7][8][9] A study by Elliott et al 5 showed that poor problem-solving abilities of the caregiver were associated with the occurrence of pressure sores and adjustment problems of the persons with SCI in the early phase of the injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, functional ability in an institutional setting may not equate with a willingness or an ability to manage in the community. Indeed the incidence of marital di culty, 6 suicide 7 and admission for avoidable post-treatment complications such as pressure sores 8 is testament to the fact that variables other than practical ability a ect global adjustment to spinal cord injury. Valid and reliable assessment of social adjustment and quality of life are both less well de®ned and more di cult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…10 ± 13 Crewe and Krause 12 surveyed individuals with SCI in 1974, 1985 and 1989 using the Life Situation Questionnaire (LSQ) which examined activity levels, frequency of medical treatment, ratings of satisfaction with various areas of life, and estimations of adjustment. The later surveys included most of the surviving participants of the 1974 study together with a group of more recent injuries.…”
Section: Introductionmentioning
confidence: 99%